The Response of the Magnetosphere to Changes in the Solar Wind Dynamic Pressure: 2. Ion and Electron Kappa Distribution Functions - Espinoza-Romo, C; Stepanova, M (John Wiley and Sons Inc, 2024)
The Earth s magnetosphere is filled with a collisionless plasma that exhibits non-Maxwellian particle distributions which are well described by Kappa functions. In contrast to the Maxwellian, the Kappa contains not only density and temperature but also the kappa index that allows us to characterize the energetic tails. In this study, we analyze the response of the ion and electron Kappa distributions, obtained by fitting ion and electron fluxes measured by the five THEMIS satellites, to changes of the solar wind dynamic pressure. It was found that the solar wind dynamic pressure strongly affects the values of the kappa index, and that its impact depends on the magnetic local time (MLT). In particular, there is a significant dawn-dusk asymmetry for low PSW values which is enhanced in the night side. Further, we observe a narrow partial ring-shaped structure at different azimuthal extension that divides the plasma into two clearly defined domains. The results obtained reflect the global reconfiguration of the magnetosphere caused by variations of the solar wind dynamic pressure. Kappa distribution parameters and their average values for different ranges of PSW and MLT are provided, which we believe will contribute as realistic inputs to the modeling of the magnetosphere. © 2024. American Geophysical Union. All Rights Reserved.